Identifikasi Jenis Gastropoda di Ekosistem Lamun Pantai Pandaratan Kabupaten Tapanuli Tengah Provinsi Sumatera Utara - Tengku Hannifa Husny; Amanatul Fadhilah (AQUACOASTMARINE, 2018)
Pandaratan Beach is located in Pondok Batu area, Sarudik Subdistrict and Central Tapanuli Regency which is a region full of seagrass beds with various roles for sustaining and developing aquatic biota especially Gastropods. Gastropods has an important role for nutrient cycle in the bottom of the water. The research aims to determined the diversity ofGastropods on seagrass at Pandaratan Beach. The research was conducted in Pandaratan Beach, Sarudik Subdistrict, Central Tapanuli Regency, North Sumatera Province from March until April 2018. The diversity of Gastropods can be assessed by looking from the factor ofspecies abundance and relatives, equibility index, diversity index, and domination index. The result shows 287 individuals consist of 17 families and 21 species. The most dominating Gastropods in first and second station is Polinices mammilla and in the third station is Strombus gibberulus. The value of diversity index (H’) of all stations is categorized in medium class of which score is 2,28-3,34. The value of equibility index (E) of each station is categorized in medium class of which score is 0,74-0,76. While the value of domination index (C) of all stations is categorized in low class of which score is 0,14-0,15. The diversity of Gastropods in seagrass ecosystem at Pandaratan Beach is in good condition.Keywords ; Gastropods, Seagrass, Diversity, Pandaratan Beach